Leaders need to be led: complementary followership in the context of community-driven development program - Lee, Junesoo; Chung, Jongwoo; Kim, Booyuel (Asia Pacific Journal of Public Administration, 2023)
Leadership has often been recognised as a major driver for successful team effectiveness. However, even weak leadership may lead to good team performance, and it is worth studying how weak leadership can be helped and complemented by followership. To investigate the paradoxical mechanism behind leadership – followership practices, we examined (1) multidimensional figures of leadership and followership using the multifactor leadership questionnaire (MLQ) and (2) the impacts of the combinations of leadership and followership on team performances both during and after a community-driven development (CDD) program. To that end, this study examines a rural CDD case implemented by the Korea International Cooperation Agency and the Myanmar Ministry of Agriculture, Livestock, and Irrigation. The analyses present some common patterns of how weak leadership and strong followership can lead to better performance than other combinations of leadership and followership. We conclude with theoretical and practical conditions of “complementary followership”, i.e., the complementary combinations of leadership and followership in group performance.